O programa bolsa escola na perspectiva das famílias atendidas - Maria Jose Batista Pinto (2006)
This dissertation analyses the Bolsa-Escola Program implemented by the City Hall of Belo Horizonte since 1997. This program is carried out through conditional cash transfer to families with children ranging from 06 to 15 years of age e whose monthly per capita income is inferior to R$85.00 (eighty-five reais). Families that are granted this benefit must ensure that their children keep a monthly school attendance record equal or superior to 85%. Today, Belo Horizontes Bolsa-Escola is implemented in all regions of the city and assists more than eleven thousand families, transferring R$168.00 (one hundred sixty- eighty reais) monthly to each family, regardless of the number of members or school-aged children. This research presents an analysis of that Program from the perspective of the beneficiary families, investigating how it resounds among them, as well as what changes it brings about in their lives. Hence, guided by a qualitative approach, we firstly conducted an exploratory research about the Bolsa-Escola Program, which allowed us to understand the dynamics of the Program and helped us in the process of selecting the families that contributed to this research. Six families were selected in the Barreiro Region, one of the regions with the largest concentration of poor families and which was also one of the first regions where the Bolsa-Escola was implemented. We conducted interviews with the families in their own homes, which enabled us to know their housing and living spaces. The collected data showed the realities of those families, whose living conditions clearly illustrate the situation of inequality in our society: poor housing and nutrition, lack of health care services, insufficient basic sanitation, precarious public transportation service, in short, social trajectories marked by the disrespect to the rights that guarantee a dignified life to any citizen. Within this context, those families showed their effort and strategies to ensure that their children have the right to Education. However, they do not always achieve this objective due to the various challenges they are faced with, such as the tendency of their adolescent children to drop out of school in order to work. We found out that the Bolsa-Escola Program changes the living conditions of those families, offering them an increase in their monthly income, providing them with access to some basic needs, such as clothing and food. The Program, however, does not transform the lives of those families, because it functions as an aid, minimizing the effects of the problem, but not addressing its causes. We also observed that the Bolsa-Escola causes changes of a qualitative nature regarding how the families keep track of their childrens school attendance. But this process does not result in change concerning the right to Education in its plenitude, remaining limited to a single aspect only. Furthermore, we found out that the Bolsa-Escola, by failing to assist all families that fit the programs criteria, fosters discrimination among the population.